Sustaining, Forming, and Letting Go of Friendships for Young People with Inflammatory Bowel Disease (IBD): A Qualitative Interview-Based Study. (4th September 2020) - Rouncefield-Swales, Alison; Carter, Bernie; Bray, Lucy; Blake, Lucy; Allen, Stephen; Probert, Chris; Crook, Kay; Qualter, Pamela
Abstract : Inflammatory bowel disease (IBD) is an incurable, chronic, gastrointestinal condition that can constrain young people's social relationships. Few studies have specifically explored friendships of people with IBD. This qualitative, participatory study used interviews, photographs, and friendship maps to explore friendships and friendship networks of young people with IBD. An online Young Person's Advisory Group was actively engaged throughout the study. Thirty-one young people participated (n = 16 males, n = 15 female; n = 24 Crohn's disease, n = 6 ulcerative colitis, n = 1 IBD-unclassified; the mean age at study was 18.7 years; range 14-25 years). Findings present a metatheme "The importance and meaning of friendships" and three interwoven subthemes of "Sustaining friendships, " "Forming new friendships, " and "Letting go of friendships." Friendship was important to the young people with IBD, providing support, but associated with challenges such as disclosure. Such challenges could be mitigated by clearer conversations with clinicians about friendships and more extensive conversations about friendships and long-term conditions in education settings.